Los factores del clima organizacional y su relación con el desempeño laboral de los servidores públicos de la Prefectura de Loja periodo mayo 2021 – abril 2022 - Chamba Lapo, Erika Ariana (2022)
This research work has allowed to determine the relationship that exists between the factors of the organizational climate and the work performance of the administrative servants of the Prefecture of Loja during the period May 2021 – April 2022. For which, the following objectives were established: Establish the relationship between work performance and the factors of the organizational climate of the public servants of the Prefecture of Loja; determine the degree of satisfaction of public servants with the assigned functions; and finally, the design of an action plan that should be implemented for the correct performance of public servants. For this, a non-experimental descriptive research was carried out, and 165 servers were surveyed, using a thirty-question survey. In addition, three interviews were applied, in which administrative servants from different departments of the institution participated. The method applied for the verification of the relationship between the two variables was Pearson's correlation coefficient, through which, it was possible to show with 0.992 that between the two variables there is a positive relationship and in turn direct. Therefore, it could be affirmed that the organizational climate managed to relate in 99% in terms of the work performance of administrative servers of the Prefecture of Loja. Finally, a diagnosis was established, through which strategies were determined that allowed the design of an action plan, which proposes proposals to improve performance in those shortcomings identified throughout the study. This proposal was finally socialized to the actors participating in the human talent department, with the purpose of achieving the improvement of the organizational climate, which allows to obtain a more optimal performance of the administrative servants of the institutions